Steel resolve eaudiobook - Daniels, B.J (Cardwell Ranch: Montana Legacy, 2019)
Sometimes you can go home again. It's just not always safe . . . Mary Cardwell Savage never meant to send that letter to her ex, Chase Steele. How could she know her words would bring the gorgeous cowboy back to Big Sky, Montana—with an unstable and dangerous stalker following close behind? Now Chase wants to prove that their love deserves a second chance. And this time, nothing will keep him from his heart's desire . . . not even a killer. Contains mature themes.